Chromosome 11 allele loss in sporadic insulinoma. Issue 5 (May 1990) - Patel, P; O'Rahilly, S; Buckle, V; Nakamura, Y; Turner, R C; Wainscoat, J S
Abstract : DNA was extracted from tissue samples of three unrelated cases of insulinoma. Chromosome 11 allele loss was investigated using several chromosome 11 specific probes which detect restriction fragment length polymorphisms. In one case, which proved informative for many of the chromosome 11 markers, allele loss was shown on both 11p and 11q. This finding is of considerable interest as the allele loss closely corresponds to that recently reported in insulinomas occurring in the familial multiple endocrine neoplasia type 1 (MEN-1) syndrome.